The Influence of State Capital Participation and Capital Structure on Company Profitability with Company Size as a Moderating Variable : (Study on State-Owned Enterprises Assigned to Infrastructure Projects for the Period 2019-2023) - Asih Pramulia; Endri Endri (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the large allocation of State Capital Participation (PMN) to State-Owned Enterprises (SOEs) for infrastructure projects, which has not been fully accompanied by increased company profitability. Fluctuating financial performance, high debt burdens, and issues of inefficient state fund management necessitate an empirical study of the effect of PMN and capital structure on profitability, considering company size as a moderating variable. This study aims to analyze the influence of State Capital Participation (PMN) and Capital Structue on the Profitability of State-Owned Enterprises (SOEs) assigned to infrastructure projects, with Company Size as a moderating variable. The research was conducted on SOEs during the 2019–2023 period using a quantitative approach with panel data regression analysis. The data analysis employed the EViews 10.0 application using multiple regression and moderation tests to examine the role of company size in moderating the relationship between independent variables and company profitability. The results indicate that State Capital Participation positively influences profitability, while Capital Structure (measured by the Debt to Equity Ratio) has a significant negative impact. Additionally, Company Size acts as a moderating variable that strengthens the relationship between PMN and profitability but does not significantly moderate the effect of Capital Structure on profitability. This research is expected to provide insights for the government and SOE management in optimizing capital allocation and managing capital structure to enhance company profitability.